Study on Acoustic Emission Localization of Concrete Using Modified Velocity - Jiapeng Li; Lei Qin (Advances in Civil Engineering)
To improve the accuracy of the acoustic emission (AE) source localization, a new 3D AE source localization method was investigated which used a combination of the modified velocity and the 3D localization algorithm based on the exhaustive method. The wave speed has a significant effect on the AE location results. With the increase of distance, the AE signal seriously attenuated due to the anisotropy of concrete, and the measured velocity changed for various distances. The velocity-distance curves were obtained when employing different water-cement ratios (W/C) and aggregate sizes. However, the current AE location system adopted constant wave velocity. As a result, the error was tremendous. The accuracy of the localization before and after the modified velocity was compared. The 3D localization results showed that compared with the constant wave velocity, the position deviation of the modified velocity was smaller and the localization results with the modified velocity were more accurate.